Sofosbuvir and ribavirin in acute hepatitis C–infected patient with decompensated cirrhosis. Issue 49 (December 2016) - Liu, Hui; Zhang, Tong; Yan, Yan
Abstract: Background: The treatment of chronic hepatitis C virus infection has been revolutionized by the advent of direct-acting antiviral agents. However, evidence of its effects on patients with acute hepatitis C (AHC) virus infection is limited. Case summary: We report the case of a patient with decompensated cirrhosis induced by autoimmune liver disease, whose condition rapidly deteriorated following AHC virus infection. The patient received sofosbuvir and ribavirin combination treatment for 12 weeks. Serum hepatitis C virus RNA remained undetectable 36 weeks after discontinuing sofosbuvir and ribavirin. Conclusion: Our findings support the use of sofosbuvir and ribavirin as a treatment in AHC patients with decompensated cirrhosis.